Energy-efficient scheduling of multiple manufacturing factories under real-time electricity pricing - Zhang, Hao; Zhao, Fu; Sutherland, John W. (CIRP annals, 2015)
Manufacturing scheduling for reduced energy costs is attracting increased interest. Energy-efficient scheduling of a manufacturing factory subject to real-time electricity pricing, such as is the case with a smart grid, represents an important but challenging situation. In this paper, multiple manufacturing factories served by one utility are investigated. The total electricity cost as a function of manufacturing schedule is minimized using a distributed optimization approach, where each facility seeks to minimize its electricity cost and exchange information with the grid. Results suggest that electricity cost of the system can be reduced, and also individual electricity costs are lowered.